Fatal acute necrohaemorrhagic pancreatitis with massive intraperitoneal and retroperitoneal bleeding: a rare cause of exsanguination. (20th January 2016) - Querido, Sara; Carvalho, Inês; Moleiro, Filipa; Póvoa, Pedro
Abstract : An otherwise healthy 37-year-old man was admitted to hospital with uncontrollable vomiting and abdominal pain. Lithiasic acute pancreatitis was diagnosed on the basis of clinical symptoms along with raised serum amylase levels and compatible findings in ultrasonography and CT scan. Two Ranson criteria (lactate dehydrogenase over 350 U/L and aspartate aminotransferase over 250 U/L) were present at admission. The patient was transferred to an intensive care unit (ICU); intravenous crystalloids were prescribed and analgaesics were administered for pain relief. Unexpectedly, 10 h after ICU admission, he presented a cardiac arrest with a non-defibrillate rhythm and died after 40 min of advanced life support. An autopsy was performed and revealed acute necrohaemorrhagic pancreatitis with massive intraperitoneal and retroperitoneal haemorrhage. This case report summarises the epidemiology, pathophysiology and risk factors for fatal bleeding acute pancreatitis.